Measuring emotional intelligence in a Malaysian sample: an exploratory factor analysis - Abd Hamid, Harris Shah; Abdul Razak, Mohamad Nahar (Universiti Kebangsaan Malaysia, 2016)
Schutte et al. (1998) developed a 33-item emotional intelligence scale which they claimed to be unidimensional. Petrides and Furnham (2006) conducted factor analysis on the same scale and found 4 factors underlying the scale. Studies on emotional intelligence had been conducted in Malaysia with scales that were adopted, adapted, and developed. The dimensionality of the scales needed to be clearly demonstrated to better put the findings within the local context. This study examined the factor structure of the bilingual version of the scale (Malay translation by Abd Hamid and Kimin, 2004) using principal axis factoring with a varimax orthogonal rotation, in a Malaysian sample. The scale was administered to 187 Malaysian employees in a government agency and a college community. The analysis revealed four factors underlying the scale that matched Petrides and Furnham’s findings. Reliability was found to be good for three factors and unacceptable for one. The issues in the factor structure were discussed.